SUBJEK PENDIDIKAN DALAM PERSFEKTIF AL QURAN DAN IMPLEMENTASINYA DI MTS MUHAMMADIYAH I PEKANBARU - Radhiyatul Fithri (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2021)
The subject of education is very influential on the success or failure of education. The subject of education is the person or group of people who are responsible for providing education, so that the material being taught or delivered can be understood by the object of education. The purpose of this study was to describe the implementation of the subject of education at Mts Muhammadiyah I Pekanbaru. This research method is analytical descriptive with interviews as a data collection technique. Based on the results of the research, it can be formulated that it was found that some teachers had low personal approach so that the teacher seemed unfriendly and even indifferent to the students, lack of mastery of the material by the teacher while the students are now very smart. Less innovative, creative and varied in learning even tend to be very conventional so monotonous. There is also very little improvement in academic qualifications and self-development in the form of training activities with the aim of increasing insight and information for the progress of learning. With such teacher conditions make students very far from being a subject of education.